Newly Diagnosed Primary Open-Angle Glaucoma Randomized to 2 Trabecular Bypass Stents or Prostaglandin: Outcomes Through 36 Months. Issue 2 (December 2016) - Vold, Steven; Voskanyan, Lilit; Tetz, Manfred; Auffarth, Gerd; Masood, Imran; Au, Leon; Ahmed, Iqbal; Saheb, Hady
Abstract Purpose To examine outcomes through 36 months in phakic eyes with newly diagnosed primary open-angle glaucoma (POAG) naïve to therapy randomized to treatment with two trabecular micro-bypass stents or topical prostaglandin. Methods Subjects with POAG naïve to therapy, with intraocular pressure (IOP) ≥21 and ≤40 mmHg, were randomized to implantation of two stents or travoprost. Additional medication was to be prescribed post-treatment for elevated IOP or glaucomatous optic nerve findings. Of 101 randomized subjects, 100 subjects were followed for 24 months and 73 subjects were followed for 36 months. Follow-up on all subjects is ongoing. Results In this randomized cohort of 101 POAG subjects, 54 subjects underwent 2-stent surgery and 47 received topical travoprost. Mean pre-treatment IOP was 25.5 ± 2.5 mmHg in stent-treated eyes and 25.1 ± 4.6 mmHg in medication-treated eyes. By 3 years, mean IOP was 14.6 mmHg in stent eyes (with medication added in 6 eyes) and 15.3 mmHg in travoprost eyes (with a second medication added in 11 eyes). In the subset of eyes that did not require additional medical therapy, mean IOP was 14.5 mmHg and 15.7 mmHg in the respective groups. Ninety-one percent of stent eyes had 3-year IOP ≤18 mmHg without additional therapy (62% ≤ 15 mmHg) and 79% of travoprost eyes had 3-year IOP ≤18 mmHg (21% ≤ 15 mmHg). Safety was favorable in both groups. Conclusions In this prospective, randomized comparison of subjects with newly diagnosed POAG naïve to therapy, substantial IOP reduction with a favorable low complication rate was shown through 3 years after either 2 trabecular stents implanted as the sole procedure or topical travoprost therapy. These data suggest 2-stent implantation may be a viable initial treatment option comparable to topical prostaglandin in newly diagnosed POAG patients. Trial registration: ClinicalTrials.gov identifier, NCT01443988. Funding Glaukos Corporation, Laguna Hills, CA.